Edukasi dan Demonstrasi Pemberian Rendaman kaki Air Hangat dan Garam pada Penderita Hipertensi - Alfian Mas’ud; Musni Musni; Agustiawan Agustiawan; Andi Wahyuda Apriadi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypertension is a global health problem whose prevalence continues to increase every year. This condition is not only a major cause of cardiovascular disease but also contributes to high morbidity and mortality rates in various countries, including Indonesia. One risk factor mitigating this problem is low public awareness of the importance of routine blood pressure monitoring. Therefore, promotive and preventive efforts are needed through health education that is easy to understand and can be applied in everyday life. This community service activity aims to increase public knowledge, especially among the elderly, about hypertension and the application of simple non-pharmacological therapies. One method introduced is soaking feet in warm water with added salt. This method is considered safe, practical, and cost-effective, making it suitable for elderly people in rural communities. The activity was carried out in Mauleng Hamlet, Paccing Village, Awangpone District, Bone Regency, with 15 elderly participants. The activity method included a pre-test to determine the participants' initial level of knowledge, counseling on hypertension, direct compression using warm water and salt foot soaks, and a post-test to measure knowledge improvement. The results showed a significant increase in participants' level of knowledge. Prior to the outreach program, only 7% of respondents had sufficient knowledge about hypertension and non-pharmacological therapy. After the outreach and reinforcement program, this figure increased to 87%. These results indicate that health education combined with practical demonstrations is highly effective in increasing public knowledge. Therefore, it can be concluded that educational activities and warm salt foot soak therapy have proven effective in increasing public understanding of non-pharmacological hypertension management and have the potential for widespread implementation as a health promotion measure.